2022
DOI: 10.3389/fnagi.2022.950143
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of natural products from Traditional Chinese Medicine in depression: Potential targets and mechanisms of action

Abstract: The molecular pathology involved in the development of depression is complex. Many signaling pathways and transcription factors have been demonstrated to display crucial roles in the process of depression occurrence and development. The multi-components and multi-targets of Traditional Chinese Medicine (TCM) are uniquely advantageous in the prevention and treatment of chronic diseases. This review summarizes the pharmacological regulations of natural products from TCM in the prevention and treatment of depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In contrast, in a college student population, Qi-stagnation and balanced constitutions were significantly associated with depression ( Yap et al, 2021 ), which is similar to our findings. For depression and other emotion problems, herbal formulas have also been developed in TCM, and these formulas target the BDNF-TrkB, MAPK pathway, etc., ( He et al, 2022 ). Our study suggests that patients with SSc who have Qi-deficiency and Yang-deficiency constitutions may need psychological and emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a college student population, Qi-stagnation and balanced constitutions were significantly associated with depression ( Yap et al, 2021 ), which is similar to our findings. For depression and other emotion problems, herbal formulas have also been developed in TCM, and these formulas target the BDNF-TrkB, MAPK pathway, etc., ( He et al, 2022 ). Our study suggests that patients with SSc who have Qi-deficiency and Yang-deficiency constitutions may need psychological and emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…They play an irreplaceable role in clinical practice. 8,9 Yadanzi (Brucea Fructus) is the dried mature fruit of Brucea javanica (L.) Merr, a plant belonging to the Simaroubaceae family. It possesses functions such as heat-clearing, detoxification, antimalarial, and antidiarrheal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of them have low toxicity and high safety and possess a broad potential market. They play an irreplaceable role in clinical practice. , …”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) profits from the flexible utilization of the concepts of holistic view and diagnosis and treatment in clinical, plays a role in the treatment of multiple diseases, especially in the fight against COVID-19, which has shown the world the great potential of TCM ( Lyu et al, 2021 ; Chen et al, 2022 ). In recent years, the antidepressant effects of herbal formulas and individual components have been gradually confirmed ( Li et al, 2020 ; He et al, 2022 ). For instance, Lu et al found that the methanol extract, ethanol extract, aqueous extract, and its volatile oil of Rhizoma Cyperi have antidepressant activity ( Lu et al, 2022 ); muscone may alleviate lipopolysaccharide (LPS)-induced depression-like behaviors through TLR/MyD88 and TLR4/NLRP3 pathways ( He et al, 2020 ); Lily Bulb and Rehmannia decoction can improve depression by reducing MAO activity, increasing monoamine neurotransmitter levels and regulating the hypothalamic-pituitary-adrenal (HPA) axis dysfunction ( Chi et al, 2019 ; Zhang et al, 2021 ), a meta-analysis showed that chaihu-jia-longgu-muli-tang can ameliorate the depressive manifestations of the patients via suppressing inflammation ( Zhao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%